Hypersonic plasma setup for oxidation testing of ultrahigh temperature ceramic composites - Paterniani Rita, Cristian Cley; Miranda, Felipe De Souza; Caliari, Felipe Rocha; Rocha, Rosa; Essiptchouk, Alexei [UNESP]; Charakhovski, Leonid; Filho, Gilberto Petraconi [UNESP] (My University, 2020)
In this study, a hypersonic plasma setup was constructed based on a vortex plasma heater with prenozzle gas-dynamic insertion. The prenozzle allows the improvement of the characteristics of the vacuum system according to the necessities of the experiments. The plasma setup produces a hypersonic thermal flow, which is capable to test the thermal oxidation of ultrahigh temperature ceramics (UHTC) composites, such as zirconium diboride (ZrB2). Thereby, ZrB2 samples were prepared with a variation of 10, 20, and 30% of silicon carbide (SiC) in volume, in order to investigate the oxidation mechanisms and microstructural properties of the samples tested under hypersonic thermal flow. The results of the oxidation tests showed that the samples with 10 and 30% of SiC undergo to the active oxidation and forms an unstable and fragile ZrO2 oxide. The formed ZrO2 does not withstand the drag force and the thermal flux of the hypersonic plasma jet, partially volatilizing the oxide layer, causing an accentuated loss of mass. For the oxidation tests of the sample with 20% of SiC, the gain of mass was observed due to the formation of ZrSiO4 passivation layer, which is a stable oxide and promotes mechanical resistance, and low degradation rate. These results can be associated with the variation of SiC, which demonstrates an ideal proportion of 20% of SiC in ZrB2, which influences the oxidation mechanisms and produce a protective layer.